Asbāb al-Nuzūl and The Rules of Interpretation: Some Notes on M. Quraish Shihab’s Views - Usman, Abur Hamdi; Avivy, Ahmad Levi Fachrul; Bin Abdullah, Mohd Farid Ravi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
An analysis of the popularity and respectability of the exegetical sub-genre asbāb al-nuzūl (occasions of revelation) in the Qur’an is usually regarded to be considered under the category of Qur’anic sciences, which is an intersection between exegesis and narration. With the tool of asbāb al-nuzūl, the exegetes obtain a structural rule that lets them supervise the verse. Furthermore, because of the problems attended upon taking a strictly historical view of asbāb al-nuzūl, Muslim scholars sometimes interpret an asbāb al-nuzūl to mean not an actual historical event, but any situation to which given Qur’anic verses might have application. Therefore, this study aims to hunt a detailed inspection of the rule of interpretation, which is related to asbāb al-nuzūl applied by M. Quraish Shihab (b. 1944), who was a prolific Indonesian exegete and his published works continue to exert a strong influence. Therefore, to arise a reasonably effortless question: what are the rules contracted to fulfil? When one knows about the asbāb al-nuzūl, it is still to be decided whether the revelation has a specific implication for the particular occasion it was connected with, or whether it is of a general implication and needs to be applied by Muslims at all times. In this vein, by applying a document with an analytical approach, this article found two rules that were related to asbāb al-nuzūl used by Shihab to ensure that the resulting exegesis was following the requirements of Islamic law. Both of these rules emphasise that the most authentic and preferable rule according to majority of the scholars, which is the ruling should be derived based on the generality of the text and not on the particularity of the reason.